THE IMPACT OF LABOUR, WAGE, AND HUMAN DEVELOPMENT INDEX ON ECONOMIC GROWTH - Marlida, Salma; Prasetyo, Ari (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2023)
Introduction: This study aims to estimate the impact of Labor Level, Wage Level, and Human Development Index on economic growth in DKI Jakarta Province between 2012 and 2021. Methods: This study employed quantitative research methodologies utilizing secondary data as its data source. Central Statistical Agency data on GRDP, Human Development Index, Manpower, and Provincial Minimum Wages were gathered (www.bps.go.id). This study used a multivariate linear regression model to determine the impact of variables using the Least Squares Equation. Results: The results of this study reveal that the macroeconomic variables HDI, Labors, and Wages have no substantial influence on GRDP. Conclusion and suggestion: To influence the increase or reduction in the level of economic growth, however, the rate of economic growth (GRDP) is not only affected by macroeconomic variables but also by religiosity-related factors.